Karakteristik Fisika dan Kimia pada Tanah Ultisol di Lahan Perkebunan Karet di Desa Gunung Kupang Provinsi Kalimantan Selatan - Syahputera, Aulia; Haris, Abdul; ㅤ, Ratna (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2024)
Soil properties are the inherent characteristics of soil bodies in different locations that are influenced by factors such as mineral composition, structure, texture, and organic content. Soil has characteristics that affect the growth of the plants that are cultivated. This study aims to determine the physical and chemical characteristics of Ultisol soil at a depth of 0-50 cm on rubber plantation land in Cempaka District, Banjarbaru City. This research was conducted in the laboratory of ULM Soil Department. The land used was in Gunung Kupang, Cempaka Village, Cempaka District, Banjarbaru City, South Kalimantan Province. The research method used in this study is an exploratory descriptive method whose implementation is carried out directly at the research site and continued with soil sampling as material for analysis in the laboratory. Soil sampling was purposefully determined in 10 minipits in rubber plantations with two sides of observation at five depths, namely 0-10 cm, 10-20 cm, 20-30 cm, 30-40 cm, and 40-50 cm. Thus, all observations amounted to 100 samples. The data analysis used is presented in graphical form and analyzed descriptively. The results of this study show that increasing soil depth causes changes in soil physical characteristics. Physical characteristics of soil texture values affect the value of bulk density, particle density,and soil moisture content. The phenomenon of changes in physical characteristics ultimately affects the chemical characteristics of C-organic, soil pH, N-total, P-total and K-total values.